The State public sector and the competencesof the territorial entities in Colombia - Sanchez-Cubides, Pedro Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The State, through the agencies and entities that integrate it, aims to look for general interest and welfare, for which, regardless of its form and organization, it must guarantee the citizens right in order to protect the human dignity. Process whereby, in the case of Colombia, municipalities, districts and departments, as the associative territorial schemes exercise a leading role, task that every time is made more efficient and effective to the extent that the nation has carried out the process of distribution of competences with the territorial entities in different sectors.